Meta-Analysis the Effects of Hypertension, High Density Lipoprotein, and Diabetes Mellitus on the Risk of Stroke - Najlah Amalia; Vitri Widyaningsih; Burhannudin Ichsan (Indonesian Journal of Medicine, 2023)
Background: Stroke is defined as an interruption of the blood supply to the brain which is usually caused by a blockage by a blood clot. This causes disruption of the supply of oxygen and nutrients to the brain resulting in damage to brain tissue. This study aims to analyze and estimate the effect of hypertension, high-density lipoprotein, and diabetes mellitus on the risk of stroke. Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flow chart and the PICO model. Population: adults. Intervention: hypertension, high-density lipoprotein, and diabetes mellitus. Comparison: normal blood pressure, normal HDL, and normal blood sugar. Outcome: strokes. The databases used were PubMed, Google Scholar, Science Direct, and Proquest with keywords (hypertension OR "diabetes mellitus" OR "high-density lipoprotein") AND stroke AND ("cross-sectional" OR "case-control") AND aOR. There were 9 Case-Control studies and 4 Cross-Sectional studies published in 2013-2023 that met the inclusion criteria. Analysis was performed with RevMan 5.3. Results: 13 studies from Oman, Iran, Lebanon, Ghana, Finland, Nigeria, China, Japan, and Saudi Arabia were selected for meta-analysis. Total sample was 71,037. Had history of hypertension (aOR= 5.48; 95% CI = 2.26 to 13.32; p= 0.002) and diabetes mellitus (aOR = 1.93; 95% CI= 1.45 to 2.57; p< 0.001) increased the risk of stroke. High HDL levels reduced the risk of stroke (aOR = 0.46; 95% CI = 0.27 to 0.79; p= 0.004). Conclusion: History of hypertension and diabetes mellitus increase the risk of stroke. However, high HDL levels reduce the risk of stroke. Keywords: hypertension, high-density lipoprotein, diabetes mellitus, stroke.